Evaluation of Holdaway Soft Tissue Analysis for Iraqi Adults with Class I Normal Occlusion - Manar Y Abdul-Qadir; Alaa' D Al-Dawoody; Ne'am F Agha (University of Mosul, College of Dentistry, 2008)
Aims: To determine cephalometric standards for Iraqi adults using Holdaway soft tissue analysis. Materials and Methods: The sample comprised 60 individual (31 males and 29 females), aged 18-23 years. Ten linear and tow angular parameters were measured on lateral cephalometric radiographs, using the definitions provided by Holdaway. For each variable mean and SD were calculated, in addition independent samples t- test was performed to detect sexual dimorphism. Results: Some differences were determined when the measurement obtained for Iraqi sample were compared to Holdaway norms. Iraqi adults showed a more obtuse H angle, less nose prominence, more upper lip strain, more skeletal convexity, and greater soft tissue chin thickness. In addition, a comparison between males and females revealed a significant sexual dimorphism for upper lip sulcus depth, upper lip thickness, basic upper lip thickness, and soft tissue chin thickness. Conclusions: soft tissue cephalometric norms are specific for each ethnic group. The normative data for Iraqi population should be used as a guide for diagnosis and planning of orthodontic treatment